The Impact of Different Types of Tests in EFL Writing on the Teachers’ Classroom Practices - Shofiya, Arina (Celt: A Journal of Culture, English Language Teaching & Literature, 2019)
To promote the quality of national education, a test, especially high-stake test, has received special concern from the government. Such kind of test brings serious consequence (impact) to some related parties like teachers, students, school systems, and society. This article is intended to highlight how different type of testing affects the teachers’ teaching practices in the classrooms. In Indonesian secondary schools, two types of tests, National Examination (NE) and School Examination (SE) are administered to measure students’ achievement in a particular level as well as to decide students’ graduation. The two tests are different at some points. First, the test for NE was developed and administered by the government through the Board of National Education Standard. Meanwhile, the preparation and administration of the test for SE were done by the English teachers at every school. Second, the test of NE was in the form of objective test, whereas, the test of SE is subjective in which the students should create writing products. Using descriptive qualitative research design, the current research investigated how four Indonesian secondary school teachers carried out the teaching of EFL Writing in their classroom as the impact of the two types of test. The findings of this research revealed that the administration of the different types of tests brings different impacts on the preparation and classrooms practices in which the teachers were more enthusiastic and serious to prepare for the SE rather than the NE. It can be concluded that a particular type of test which requires full involvement of the teachers either in the preparation or the administration like SE brings positive impact on their classroom practices.